High Serum Vitamin B12 Levels Associated with C‐Reactive Protein in Older Patients with Cancer. (19th August 2020) - Couderc, Anne‐Laure; Puchades, Eddy; Villani, Patrick; Arcani, Robin; Farnault, Laure; Daumas, Aurélie; Courcier, Anais; Greillier, Laurent; Barlesi, Fabrice; Duffaud, Florence; Salas, Sébastien; Costello, Régis; et al.
Abstract: Background: A Comprehensive Geriatric Assessment (CGA) has been proposed to assess prognosis and to adapt oncological care in older patients with cancer. However, few biological markers are incorporated in the CGA. Methods: This comparative study on older patients with cancer was realized before final therapeutic decision and during a CGA that included biological markers. Our objective study was to know if the serum vitamin B12–C‐reactive protein index (BCI) can help to estimate early death and unplanned hospitalization. Associations between BCI and unplanned hospitalization or mortality were analyzed using ordered multivariate logistic regression. Findings: We included 621 older cancer adults in outpatient care with a median age of 81 years (range, 70–98 years) from September 2015 to May 2018. In this study, 5.6% of patients died within 3 months, 8.8% had unplanned hospitalization within 1 month, and 11.4% had unplanned hospitalization within 3 months. Hypercobalaminemia was present in 83 patients (13.4%), and 34 patients (5.5%) had BCI >40, 000. According to the multivariate analysis, BCI was a prognostic factor of mortality within 3 months and unplanned hospitalizations at 1 and 3 months. Impaired activities of daily living (ADL) and palliative care were also risk factors for mortality within 3 months. Impaired instrumental ADL, low albumin level, and palliative care were risk factors for unplanned hospitalization at 1 month. Interpretation: BCI could be routinely added to the CGA process, as part of a pretreatment workup, in order to assess more precisely the frailties and to adapt oncological care in older patients treated for cancer. Implications for Practice: Aging comes with an increase of frailties and comorbidities. To identify frailties in older patients with cancer, this study used a Comprehensive Geriatric Assessment, which allowed for the adaptation of each treatment plan in accordance with the individual needs of the patients. However, biological characteristics were not included in this assessment. This study showed that hypercobalaminemia and vitamin B12 ‐C‐reactive protein index may be potential markers for cancer with poor prognosis, particularly in the older population. These biological markers can be used in geriatric oncology and general medicine. Abstract : The development of the Comprehensive Geriatric Assessment has improved the management of older patients with cancer. This article suggests the need to include biological markers, focusing on high serum vitamin B12 levels and the vitamin B12/C‐reactive protein index a possible prognostic indicators in older patients treated for cancer.